Decoding Digital Culture Congruence in Canada and India - Rameez, Naveeda (Global journal of Business and Integral Security, 2024)
In this study, we delve into the multifaceted realm of marketing strategies employed by Over-the-top (OTT) platforms, focusing on Netflix, Amazon Prime, and Disney+ Hotstar in Canada and India. Our primary objective is to elucidate how these strategies contribute to expanding user bases and enhancing market penetration within these diverse geographical regions. We set out several research objectives, including investigating the impact of influencer endorsements on digital marketing campaigns, contrasting personal preferences regarding digital marketing usage on OTT platforms, examining the frequency of adaptation of digital marketing plans by businesses in Canada and India, assessing the influence of modified digital marketing tactics on consumer streaming hours, and evaluating the digital consumption habits of audiences in India and Canada on behalf of broadcast companies. My research questions aim to unravel the nuanced dynamics of user behaviour and preferences in the context of online video services, particularly among the millennial demographic in India and Canada. We explore the divergence in behavioural influences across borders and the impact of evolving marketing strategies, such as influencer marketing, cross-platform marketing, and personalised marketing, on millennial content consumption and behaviour patterns. Adopting a descriptive methodology, I utilize a pre-designed questionnaire to investigate consumer preferences and time allocation for OTT content consumption among millennials. Ethical considerations remain paramount, with measures in place to ensure informed consent, confidentiality, and the protection of participant rights. Additionally, I employ thematic analysis as a qualitative method to interpret the gathered data, allowing for a deeper understanding of participants' perspectives and experiences. In conclusion, this study contributes to the ongoing discourse surrounding the impact of OTT services on millennials while shedding light on the intricate interplay between marketing strategies and user behaviour. The findings offer valuable insights that can inform both academic understanding and practical application in the ever-evolving landscape of digital entertainment and marketing.